“The Brain That Fell Out Of the Skull”. Hourglass of Danilo Kiš as an Illness/Disease Narrative about Stray Rationalism - Silvija Novak Bajcar (Institute for Literature and Art, 2020)
The central place of Danilo Kiš’s novel Hourglass, which is a kind of an illness/disease narrative (écriture patografique), is occupied by the human condition as an animal rationale. It was one of the subjects raised by many intellectuals, including Edmund Husserl, whose name does not appear here accidentally. Phenomenology was a strong intellectual impetus for the authors of the new French novel. Although in his statements Kiš resolutely distanced himself from any connections with him, emphasizing the documentary, auto/biographical character of his work, in this article I point to the existent (albeit unintended) connections between Kiš’s novel and the literary views of his French colleagues.